2018
DOI: 10.1111/cas.13482
|View full text |Cite
|
Sign up to set email alerts
|

New metformin derivative HL156A prevents oral cancer progression by inhibiting the insulin‐like growth factor/AKT/mammalian target of rapamycin pathways

Abstract: Metformin is a biguanide widely prescribed as an antidiabetic drug for type 2 diabetes mellitus patients. The purpose of the present study was to observe the effects of the new metformin derivative, HL156A, on human oral cancer cell and to investigate its possible mechanisms. It was observed that HL156A significantly decreased FaDu and YD‐10B cell viability and colony formation in a dose‐dependent way. HL156A also markedly reduced wound closure and migration of FaDu and YD‐10B cells. We observed that HL156A de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…IGF-1 (insulin-like growth factor) is upstream of the Akt pathway, which is linked to cell survival. When IGF-1 binds with the IGF-1 receptor, Akt phosphorylation occurs [ 18 ], thereby initiating mTOR (mammalian target of rapamycin) phosphorylation [ 19 21 ]. The phosphorylation of mTOR leads to the activation of S6K and 4EBP1, which inhibits excessive autophagy to maintain basal autophagy (homeostasis) in young MSCs [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1 (insulin-like growth factor) is upstream of the Akt pathway, which is linked to cell survival. When IGF-1 binds with the IGF-1 receptor, Akt phosphorylation occurs [ 18 ], thereby initiating mTOR (mammalian target of rapamycin) phosphorylation [ 19 21 ]. The phosphorylation of mTOR leads to the activation of S6K and 4EBP1, which inhibits excessive autophagy to maintain basal autophagy (homeostasis) in young MSCs [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A new metformin derivative, IM156, targets slow-cycling tumor cells that tend to escape from treatment with conventional chemotherapies that have been designed to target fast-cycling cells. In addition, IM156-mediated inhibition of mitochondrial function prevents the growth of oral cancer and glioblastoma [ 176 , 177 ]. Although the above-mentioned therapeutics have been demonstrated to reduce mitochondrial function and survival of CSCs, it should be considered that inhibition of a single specific component of OXPHOS and ATP production may induce alternative pathways, precluding the efficacy of regimens to ultimately eradicate CSCs.…”
Section: Therapeutic Strategies Targeting Cscsmentioning
confidence: 99%
“…Moreover, with respect to antitumor activity, the new metformin derivative HL156A can inhibit the growth of human oral cancer cell lines, and 40 μM HL156A resulted in 45% cell growth inhibition at 24 hr which greatly improved the antitumor activity in comparison with the parent compound. It was observed that HL156A significantly downregulated p‐mTOR and enhanced p‐AMPK expression . Furthermore, the new biguanide derivatives that were designed and synthesized on the basis of the arylmethylbiguanide scaffold of phenformin showed significantly stronger inhibition on cancer cell growth than phenformin and exhibited remarkable antiangiogenic effects .…”
Section: Resultsmentioning
confidence: 99%